2022
DOI: 10.3389/fsurg.2022.834551
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Ponticulus Posticus: A Narrative Literature Review

Abstract: Study DesignNarrative review.ObjectiveThe purpose of this review was to consolidate the current literature related to ponticulus posticus (PP) and to improve the systematic understanding of this anatomical variant of atlas among spine surgeons.MethodsArticles reviewed were searched in PubMed, Ovid MEDLINE, and Embase. All articles of any study design discussing on PP were considered for inclusion. Two independent authors read article titles and abstracts and included appropriate articles. The relevant articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Another study [19] showed that, apparently, it is unrelated to the skeletal malocclusion type or dental anomalies and indicates the congenital hypothesis of PP's origin already reported in the literature. A narrative review [20] that included 113 articles showed that the PP compresses the third segment of the vertebral artery, the suboccipital nerve, and the venous plexus, consequently contributing to the incidence of neurological pathologies. When a PP is observed or suspected on a lateral radiograph, it is recommended that a computed tomography (CT) scan of a patient who is about to receive a C1 lateral mass screw be performed, which could determine a safe entry point and the right trajectory of the screw insertion [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another study [19] showed that, apparently, it is unrelated to the skeletal malocclusion type or dental anomalies and indicates the congenital hypothesis of PP's origin already reported in the literature. A narrative review [20] that included 113 articles showed that the PP compresses the third segment of the vertebral artery, the suboccipital nerve, and the venous plexus, consequently contributing to the incidence of neurological pathologies. When a PP is observed or suspected on a lateral radiograph, it is recommended that a computed tomography (CT) scan of a patient who is about to receive a C1 lateral mass screw be performed, which could determine a safe entry point and the right trajectory of the screw insertion [20].…”
Section: Discussionmentioning
confidence: 99%